The Dynamics of PMO in Construction Companies: A Critical Review - Veronika, Alin; Latief, Yusuf (Avenew Indonesia, 2025)
The construction sector has seen Project Management Offices (PMOs) become indispensable, charged with the duty of synchronizing project management techniques with the strategic goals of the organization. As the intricacies of construction projects increase, it is imperative to evaluate the functions, advantages, and obstacles related to PMOs. This analytical review amalgamates current scholarly work to investigate the manner in which PMOs facilitate strategic alignment, operational effectiveness, and the incorporation of technology within construction enterprises. Through a thorough examination of existing literature, the research delves into multiple facets of PMO execution, encompassing strategic functions, operational efficiency, workforce dynamics, technological assimilation, and regulatory frameworks. The results demonstrate that PMOs considerably bolster project management proficiency by harmonizing resources with corporate objectives and refining operational workflows through technological innovations. Nevertheless, challenges remain, such as organizational resistance, bureaucratic inertia, and the hurdles PMOs encounter in evidencing measurable value. These obstacles underscore the necessity for flexible PMO frameworks that integrate Agile practices and utilize emerging technologies such as artificial intelligence and machine learning. Such innovations could enhance predictive capabilities and inform decision-making processes. To fully harness the potential of PMOs, forthcoming research should prioritize the establishment of comprehensive models for assessing PMO efficacy and improving stakeholder engagement approaches. By proficiently articulating the value of PMOs and ensuring their alignment with organizational strategies, construction firms can evolve PMOs from mere administrative support roles into strategic collaborators that foster competitive advantage and sustainable development. This review offers a strategic guide for the effective utilization of PMOs, stressing the significance of aligning their organizational structure with corporate strategies and the dynamic demands of the industry. Through persistent innovation and strategic coherence, PMOs can play a crucial role in enhancing the success and sustainability of construction initiatives within the increasingly competitive global landscape.